THERMODYNAMIC PROPERTY MODEL OF WIDE-FLUID PHASE n-BUTANE - Chan Sarin; I Made Astina; Prihadi Setyo Darmanto; Haruki Sato (Mesin, 2007)
New thermodynamic property model for n-Butane expressed in form of the Helmholtz free energy equation is presented. The formulation consists of eight terms of the so-called ideal-gas part and eighteen terms of the residual part. This is a relatively short equation in comparison to the existing equations, which are widely accepted, including the newly published in year 2006. In its development, available accurate experimental data of fluid properties and theoretical approach from the intermolecular potential were simultaneously considered to insure accuracy and to improve reliability of the equation of state over wide range of pressures and temperatures, especially at low temperatures in which the refrigeration field is concerned. From the coverage of experimental data used in model's development, the validity range is then from triple-point (134.895 K) to temperature of 589 K and pressure up to 69 MPa. The uncertainties with respect to different properties are estimated to be 0.02% in ideal-gas isobaric specific heat, 0.2% in density, 1% in heat capacities, 0.2% in vapor-pressure except at very low temperatures, 0.05% in saturated-liquid density, 0.02% and 0.8% in speed of sound in the vapour and liquid phases, respectively.